Advanced multi-criteria decision making for addressing complex sustainability issues - Chatterjee, Prasenjit 1982-; Yazdani, Morteza (A volume in the Advances in environmental engineering and green technologies (AEEGT) book series, 2019)
"This book examines different types of decision-making modeling in addressing complex sustainability issues in the areas of economics, business, manufacturing, management, and mechanical engineering"--